Arbeitskräfteüberlassung in Österreich: Eine empirische Untersuchung zur Entwicklung der Arbeitskräfteüberlassung im Zeitverlauf und zum Status quo der Arbeitssituation der beschäftigten Personen - Andreas Riesenfelder; Lisa Danzer; Petra Wetzel (Verlag des ÖGB GmbH, 2018)
Keine andere Branche konnte in den letzten Jahren eine derart starke Expansionsdynamik verzeichnen wie jene der Leiharbeit bzw. Arbeitskräfteüberlassung. Vorliegende Studie stellt eine empirische Untersuchung zur Entwicklung der Arbeitskräfteüberlassung im Zeitverlauf sowie zum Status Quo der Arbeitssituation der beschäftigten Personen dar. Geprüft wird, inwieweit LeiharbeiterInnen noch immer ArbeitnehmerInnen zweiter Klasse sind bzw. ob der Gap zwischen Kern- und Randbelegschaften mittlerweile verkleinert werden konnte. Zusätzlich kommen LeiharbeiterInnen im Rahmen einer repräsentativen Befragung selbst zu Wort. – – The research project is based on five work packages: contextual information was gathered through literature and legal text analysis and research reports as well as in qualitative interviews with works council members. In addition to representative interviews with temporary agency workers, the empirical work also includes analyses of consensual terminations over time, based on the data of regional health insurance providers (Gebietskrankenkassen), and of contribution controlling for termination fees, as well as in-depth longitudinal analyses for the period between 1997 and 2016 on the basis of L&R Sozialforschung's labour market and employment careers database. Regarding the genesis of temporary agency work in Austria, the first major milestone to be emphasized is the enactment of the Temporary Agency Work Act (Arbeitskräfteüberlassungsgesetz, AÜG) in 1988, which aimed to protect leased workers. Years of negotiation between the social partners finally resulted in the signing of a collective agreement for the temporary agency work industry in 2002, which in particular regulated the issues of remuneration claims and continued remuneration in lease-free periods, and reduced legal uncertainties for both employees and employers. (...)
Keywords: 300